2018
DOI: 10.1111/bcpt.13123
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for linezolid‐induced thrombocytopenia in patients without haemato‐oncologic diseases

Abstract: This study aimed to describe the occurrence and to evaluate the predictive factors of thrombocytopenia caused by parenteral linezolid in hospitalised patients without haemato-oncologic diseases. Using electronic medical records, a retrospective safety evaluation was performed among all hospitalised adult patients who received parenteral linezolid therapy between January 2005 and June 2016. Of all identified 264 patients with an average age of 63.4 (SD 15.8) years, thrombocytopenia occurred at a rate of 29.2% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 24 publications
9
59
3
Order By: Relevance
“…41 Linezolid-associated thrombocytopenia was observed in 2.4% of clinical trial participants 42 ; however, postmarketing studies have since reported higher rates, ranging from 17.6% up to 48.4%. [43][44][45][46] Among cancer patients, specifically, linezolid-associated thrombocytopenia occurred in 14.1% to 34.1% of patients. 46,47 Linezolid is generally well tolerated even with higher dosing if duration is maintained at 7 days or less.…”
Section: Linezolid In Perspectivementioning
confidence: 99%
“…41 Linezolid-associated thrombocytopenia was observed in 2.4% of clinical trial participants 42 ; however, postmarketing studies have since reported higher rates, ranging from 17.6% up to 48.4%. [43][44][45][46] Among cancer patients, specifically, linezolid-associated thrombocytopenia occurred in 14.1% to 34.1% of patients. 46,47 Linezolid is generally well tolerated even with higher dosing if duration is maintained at 7 days or less.…”
Section: Linezolid In Perspectivementioning
confidence: 99%
“…One study [9] showed that carbapenem combination therapy and low baseline platelet count were signi cant predictors, and the duration of linezolid administration or renal function had little effect. However, a study conducted by Choi et al [11] revealed that low-dose aspirin was a possible risk factor, and the effect of carbapenem combination therapy was not signi cant.…”
Section: Introductionmentioning
confidence: 96%
“…Although under longer treatment durations, linezolid-treated patients had a higher potential for lower platelet counts compared to the comparator, the difference was not statistically signi cant. However, emerging observational studies have demonstrated the thrombocytopenic effect of linezolid [4][5][6][7][8][9][10][11][12][13]. Depending on different de nitions of thrombocytopenia, the incidence of thrombocytopenia ranged from 16.7-48.4% in adults treated with intravenous or oral linezolid [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations